Eksistensi dan kedudukan hukum ekonomi syariah di indonesia - Marreta, Rani (Maliki Interdisciplinary Journal, 2025)
Indonesia is one of the countries with the largest Muslim population in the world, therefore Indonesia is known to be quite likely to become a country with the highest development in the value of Islamic economic assets in the world. Sharia-based economy develops along with the birth and development of Islam in the world (Mahdi, 2021). Islamic economic law in Indonesia has experienced significant development along with the increasing public awareness of the importance of sharia principles in various aspects of life, including the economy. Pancasila as the foundation of the Indonesian state provides a foundation for the application of sharia economic law, which focuses on justice, balance, and blessings in economic transactions. challenges to the existence and position of sharia economic law in Indonesia require serious attention from various parties, including the government, academics, and the community. With the right approach, it is expected that sharia economic law can function effectively and provide significant benefits to the wider community.